I got in! : the ultimate college audition guide for acting and musical theater - Dennard, Mary Anna (Mary Anna Austin Dennard, 2018)
Nationally recognized college audition coach Mary Anna Dennard shares her expertise on how to prepare for the highly competitive college audition process. Included are: exclusive audition tips from college auditors, list of colleges with performing arts degrees, guidance on monologues, songs, wardrobe, head shot and resume, how to schedule college auditions.